The Cxcr2+ subset of the S100a8+ gastric granylocytic myeloid-derived suppressor cell population (G-MDSC) regulates gastric pathology - Kao, Krystal D.; Grasberger, Helmut; El-Zaatari, Mohamad (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSCs) comprise a hetergenous immune cell population that expands within the inflamed microenvironment of the stomach during pre-cancerous and cancerous lesion development in humans and animal models. Due to the heterogeneity of these cells, our understanding of their diverse functions remains lacking. For example, it has been established that MDSCs can suppress T cell function, thereby mediating an immunoregulatory effect that aids tumor growth in the context of cancer. However, the role of these cells in preneoplastic lesions, when tumors are not present, is not clear. Moreover, the heterogeneity of these cells indicates that they play uncharacterized diverse roles. It is therefore important to establish a mechanism to target the subsets of these cells and decipher their functions in animal models. In this study, we identified the calprotectin subunit, S100a8, as a global pan-marker of total gastric granulocytic MDSCs. We also identified specific markers that constitute subsets of this global population. We identified Cxcr2 + MDSCs as one of these subsets, and, as proof-of-concept, targeted this population specifically to elucidate its function. The data showed that this MDSC subpopulation regulated gastric pathology, which associated with dysregulation of lipid peroxidation. Hence, the study establishes and verifies a mechanism for studying gastric MDSC subpopulations.